The implementation of questionnaires design principles via online questionnaire builder - Saaya, Zurina; Devaraju, Anusuriya; Mustafa, Nuridawati; Chew, Choon Leong (2007)
Online Questionnaire Builder (OQB) is web-based survey software that provides complete set of tools for users to conduct the overall survey process from questionnaire design and distribution to the presentation of the survey results. This paper delivers the implementation a comprehensive set of guidelines for the design of online questionnaires via our survey software. The guidelines are drawn from relevant disparate existing studies. Implementation of the design principles are mainly concerning the survey structure, layout, navigation, formatting, response format and question types. The design principles are incorporated within the survey creation software to guide questionnaire design according to best-practice, while the benefits of online-questionnaire delivery can be achieved.